2017
DOI: 10.1080/09273948.2017.1298817
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of a Large Cohort of Patients with Eales’ Disease

Abstract: Eales' disease is a bilateral recurrent retinal vasculitis disorder and timely treatment with steroid and/or laser photocoagulation result in better visual outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
2
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 12 publications
3
16
2
3
Order By: Relevance
“…Eales' disease is a condition characterized by occlusive vasculitis and development of retinal neovascularization. Biswas et al have been instrumental in providing an update on the current understanding and etiopathogenesis of this condition [61,62]. Eales' disease is presently thought to be due to hypersensitivity reaction to tubercular proteins.…”
Section: Presumed Tubercular Retinal Vasculitismentioning
confidence: 99%
“…Eales' disease is a condition characterized by occlusive vasculitis and development of retinal neovascularization. Biswas et al have been instrumental in providing an update on the current understanding and etiopathogenesis of this condition [61,62]. Eales' disease is presently thought to be due to hypersensitivity reaction to tubercular proteins.…”
Section: Presumed Tubercular Retinal Vasculitismentioning
confidence: 99%
“… 2 Active periphlebitis may be accompanied by anterior uveitis, posterior uveitis, and pars planitis. 1 , 3 Patients usually present with recurrent VH and involvement is generally bilateral. 3 Although defined as an idiopathic disease, it may be associated with Mycobacterium tuberculosis and hypersensitivity to tubercular antigen.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic steroid therapy is effective in controlling the active phase of Eales’ disease. 3 Intravitreal steroids are useful in the treatment of periphlebitis and cystoid macular edema. 6 , 7 Performing early retinal photocoagulation on non-perfused areas has a positive effect on visual outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Also, late presentation was attributed to poor final outcome of disease. 5 In a separate study, evaluation of vitreous fluid of patients of ED revealed increased expression of Vascular Endothelial Growth Factor (VEGF), highlighting the possible role of intravitreal anti-VEGF in treatment and managing progression of ED. 6 Different case reports have reported efficacy of intravitreal anti VEGF injections in management of ED.…”
Section: Introductionmentioning
confidence: 99%